Influence of Social Media on Political News Credibility in Kogi State, Nigeria - Oladokun, Bolaji David; Nsirim, Onyema; Otebe, Fidelis; Agih, Abdul; Mbazu, Emmanuel Chinedu; Mohammed, James Dada (Covenant Journal of Communication, 2023)
News content from social media comes from several platforms whose credibility, according to literature, cannot be vouched for, unlike the traditional sources which are subject to several editorial gatekeeping checks. Notwithstanding the credibility, it appears the influence of the conventional media as providers of information is waning particularly among young people who rely more on social media for news. This study examined political news consumption in social media by 384 respondents who completed a questionnaire to determine the source credibility in one of Nigeria’s 36 states - Kogi. Findings confirm a preponderance of news consumption in social media with the following sample means Twitter (x̄=3.23), Facebook (x̄=3.16), blog (x̄=3.05), Instagram (x̄=2.78), YouTube (x̄=2.59) and Yahoo News (x̄=2.58) for political news. Findings also show that there is a significant difference in the credibility of political news information on social media among the state’s three senatorial zones. One thing is certain: traditional media should start dropping the idea that social media sources are not credible. They should emphasize their social media strategies to reach out to more people, especially the youth. The study is useful for researchers and observers who are interested in knowing the level of trust consumers have in news sources.